1996
DOI: 10.1080/00222216.1996.11949763
|View full text |Cite
|
Sign up to set email alerts
|

Recreation as an Economic Development Strategy: Some Evidence from Utah

Abstract: An examination of employment patterns in rural Utah counties suggests that those counties that primarily rely on tourism and recreation to maintain economic viability exhibit annual employment variability much greater than those counties that rely on alternative economic activity.Compared to long-run boomlbust employment cycles, which are prevalent in counties that rely on resource extraction, annual recreation, and tourism employment cycles, are at least as variable and of much shorter duration due to the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…Mbiawa (2005) cites Ndubano (2000) and Mbiawa (2003), who found that in the rural villages of the Okavango Delta of Botswana, the majority of locals worked as unskilled labourers and earned income below the poverty line, while expatriates were typically employed in management positions and earned several times what local entrepreneurs made. Full-time employment may be particularly difficult to obtain for locals, as tourism is often seasonal in nature; this seasonality frequently leads to employment that is also seasonal (Farver 1984;Keith and Fawson 1996;Seckelmann 2002). Farver (1984) reviewed the Gambian tourism industry and found that hotels would cut over half their workforce in the low season, resulting in many employees being no better off than they were in farming.…”
Section: Lack Of Employmentmentioning
confidence: 99%
“…Mbiawa (2005) cites Ndubano (2000) and Mbiawa (2003), who found that in the rural villages of the Okavango Delta of Botswana, the majority of locals worked as unskilled labourers and earned income below the poverty line, while expatriates were typically employed in management positions and earned several times what local entrepreneurs made. Full-time employment may be particularly difficult to obtain for locals, as tourism is often seasonal in nature; this seasonality frequently leads to employment that is also seasonal (Farver 1984;Keith and Fawson 1996;Seckelmann 2002). Farver (1984) reviewed the Gambian tourism industry and found that hotels would cut over half their workforce in the low season, resulting in many employees being no better off than they were in farming.…”
Section: Lack Of Employmentmentioning
confidence: 99%
“…oil and gas extraction, mining, and heavy industry tend to far outstrip the capacity of local rural labour markets and draw migrant workers on a regional, national and global scale (Freudenburg and Wilson, 2002;Gramling and Freudenburg, 2006;Johannesson, 2010;Schafft et al, 2013;Tonts, 2010). Similar to the seasonal cycles in more traditional extraction industries, the growth in tourism has further contributed to occupational mobility through seasonal labour shortages in the high season and underemployment in the low season (Boffa and Succurro, 2012;Bosworth and Farrell, 2011;Johannesson et al, 2010;Keith et al, 1996).…”
Section: Introductionmentioning
confidence: 93%
“…This is espedally true for the highest paying jobs (Mbaiwa 2005). Full time employment may be particularly difficult to obtain for locals, as tourism is often seasonal in nature and thus many jobs are seasonal as well (Keith and Fawson 1996;Seckelmann 2002).…”
Section: Souvenirs and Economic Developmentmentioning
confidence: 98%